Identification of climate adaptive multivariate optimization methodologies for the design of NZEB in India: a holistic review - Chaturvedi, Pushpendra Kr.; Kumar, Nand; Lamba, Ravita (Frontiers in Energy Efficiency, 2024)
Net zero energy building (NZEB) is an efficient approach to pull up the world's sustainable development and climate mitigation. This paper provides a comprehensive review of multiobjective optimization (MOO) based case studies of NZEB design. The critical analysis focused on the "3Ps" criterion of sustainability, which encompasses social, environmental, and economical aspects with protecting the people, planet, and profit. This study identifies the gaps in exploring MOO techniques-based case studies for decision-making of NZEB design in India and its requirements. Moreover, it demonstrates various passive-design strategies, energyefficient technologies, and renewable energy and their impact on occupant comfort, energy model, and building life cycle. It presents global needs and requirements of NZEB's, definitions of NZEB in different countries, and their policies. This review suggests a four-step methodological framework for NZEB design in India. It provides the potential and reliability of various algorithms, tools, and simulation engines to solve building problems. The presented framework can aid designers in the decision-making of NZEB designing, refurbishment, and renovation. Moreover, this work highlights the future research direction and potential challenges for implementing the proposed framework in India.